Predictive model of grinding residual stress for linear guideway considering straightening history. (15th June 2020) - Ling, He; Yang, Changmei; Feng, Shichong; Lu, Hong
Highlights: Analytical models of longitudinal stress and straightening stroke are given to reveal the evolution of stress for linear guideway under pressure straightening process. Considering the straightening residual stress, an analytical model of residual stress in grinding process is established. Results turn out that the prediction model established in this paper gives more realistically residual stress distribution. Abstract: Application of linear guideway has been widely developed for its high position accuracy, movement efficiency and easy installation. The surface finishing of linear guideway by grinding process following straightening process is essential by reason of the requirement of surface roughness and movement precision. A prediction model of grinding residual stress considering initial residual stress generated by straightening process is established in this paper. Firstly, the longitudinal stress distribution of linear guideway during straightening process and a numerical method for calculating the straightening stroke are presented considering the stress-inheriting behavior. Then, an analytical model is proposed to predict the residual stress caused by grinding process with the initial stress generated by straightening process. The theoretical and finite element analysis results show that the residual surface stresses are tensile under the grinding conditions applied in this paper. Both the results obtained by theoretical and experiment results indicated that the compressive residual stress due to straightening process leads to compressive residual stress after grinding. Therefore, the initial residual stress of former process should be taken into account when studying the residual stress of linear guideway induced by grinding process. Graphical abstract: Image, graphical abstract